CSC305: Programming Paradigms / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2022)
This course provides students with the tools necessary for the critical evaluation of existing and future programming languages. Among fundamental concepts underlying the design, definition and implementation of contemporary programming languages that will be discussed in this course are programming languages structures, presenting a formal method of describing syntax and introducing approaches to lexical and syntactic analysis. This course also highlighted the key concepts of the most important programming paradigms; the long-established paradigm of imperative programming, the increasingly important paradigms of object-oriented, the more specialized paradigms of functional and logic programming and the paradigm of scripting.